ON THE OUTCOMES OF THE ALL!RUSSIAN SEMINAR "CURRENT CHALLENGES IN THE FORENSIC EXAMINATION OF TRACE EVIDENCE OF HUMAN AND ANIMAL ORIGIN” HOSTED BY THE RFCFS OF THE RUSSIAN MINISTRY OF JUSTICE (MOSCOW, APRIL 13-17, 2015) - A. Bushin (Теория и практика судебной экспертизы)
.